Crosstalk in Elliptical Sensor Arrays for Current Measurement - Zapf, Florian; Weiss, Roland; Weigel, Robert (IEEE Transactions on Instrumentation and Measurement, 2022)
Contactless current sensors that use arrays of magnetic field sensors are a good alternative to core-based current sensors because the omission of the magnetic core offers many advantages. Particularly, circular sensor arrays have proven to feature good robustness against various error sources. As rectangular bus bars are frequently used for local high-current power distribution systems, elliptic arrays would require less space than circular arrays. Up until now, no publication on magnetic interference errors of elliptic sensor arrays has been presented. This article examines the crosstalk error for different sensor distribution methods, aspect ratios, numbers of sensors, and offset angles with calculations and measurements. Therefore, an interference conductor is positioned at different angles and distances relative to the elliptic arrays. We show that the crosstalk error can be reduced with our elliptic designs in comparison to a circular design with an equal number of sensors and an equal length of the semimajor axis. The projection distribution typically offers a five times smaller crosstalk error compared to the uniform curve segment length distribution. To support the design of elliptical arrays, instructions for the optimization against interference errors for elliptic sensor arrays are given in this article. Thus, an optimal offset angle for the reduction of the crosstalk error is presented.
CRIS-Team WoS Importer:2022-04-29